2018
DOI: 10.1007/s11769-018-1012-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Susceptibility Assessment of Collapses and Landslides in the Riparian Zone of the Xiaowan Reservoir

Abstract: The southwest alpine gorge region is the major state base of hydropower energy development in China and hence planned many cascading hydropower stations. After the reservoir impoundment, the intense water level fluctuations under the interaction of cascade dams operating and the mountainous flooding, usually cause bank collapse, landslide and debris flow hazards. The Xiaowan reservoir (XWR), for example, as the 'dragon head' meg reservoir located in the middle mainstream of Lancang River, have resulted in a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Enhancing this optimization significantly improves the speed and accuracy of susceptibility map production. In this study, we employ a novel combination of data and spatial features through nine machine-learning models, alongside geographic detectors, pioneering this approach based on the foundational work cited in references [6][7][8]. Although various optimization methods ranging from simple to complex models have been explored by scholars, often yielding improved results, our approach addresses the lack of spatial interpretation inherent in many machine learning models, thereby enhancing the practical application of these optimized factors.…”
Section: The Optimization Of the Evaluation Factors Of The Seismic La...mentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing this optimization significantly improves the speed and accuracy of susceptibility map production. In this study, we employ a novel combination of data and spatial features through nine machine-learning models, alongside geographic detectors, pioneering this approach based on the foundational work cited in references [6][7][8]. Although various optimization methods ranging from simple to complex models have been explored by scholars, often yielding improved results, our approach addresses the lack of spatial interpretation inherent in many machine learning models, thereby enhancing the practical application of these optimized factors.…”
Section: The Optimization Of the Evaluation Factors Of The Seismic La...mentioning
confidence: 99%
“…In recent years, the frequency of landslides and slope instabilities has sharply increased, primarily due to the cumulative effects of rapidly changing climate conditions and heightened anthropogenic disturbances [4,5]. Landslide disasters are frequent in China, among which seismic landslides pose the most severe threats [6]. To more effectively address these disasters and promote sustainable development, the creation of Seismic Landslide Susceptibility Maps (SLSMs) is imperative [7].…”
Section: Introductionmentioning
confidence: 99%
“…This study analyzes the susceptibility of KGS from three basic conditions: karst conditions (KCs), overburden conditions (OCs), and hydrodynamic conditions (HCs). Based on ignoring factors that have little impact on basic conditions, we further decompose basic conditions into six influencing factors: bedrock lithology (KC BL ), degree of karstification (KC DK ), thickness of overburden OC T , lithology and structure of overburden OC LS , distance between groundwater level and bedrock HC DLB , and variation in groundwater level HC VL [17,[50][51][52][53].…”
Section: Moshui Lake-south Lakementioning
confidence: 99%
“…[12,13]. Several studies [14][15][16][17][18] have investigated the triggering mechanisms of KGS, using various analytical methods such as microgravity measurement, logistic regression analysis, and the information value method or experimental simulation, and found that factors such as unstable surface sediments, land development and utilization, poor surface drainage, and high surface slope can affect the occurrence of KGS. However, the above research primarily focuses on large areas and wide plain suburbs, emphasizing the KGS phenomenon's causal mechanisms and statistical laws.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the Geographical Information System (GIS) and Remote Sensing (RS) technology, geological hazard susceptibility assessments have also become more efficient and accurate, which greatly accelerates the research process in this field. The assessment methods of geological hazards mainly include the Analytic Hierarchy Process (AHP) [3][4][5][6][7], the Support Vector Machine (SVM) [8,9], the Information Value method (IV) [10,11], the Frequency Ratio method (FR) [4,12], the Weight of Evidence method (WOE) [4,13,14], Artificial Neural Network (ANN) [15][16][17], Random Forest (RF) [8,18] and a variety of model coupling methods [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%